Validity and Reliability of the Rear Foot Elevated Split Squat 5 Repetition Maximum to Determine Unilateral Leg Strength Symmetry. Issue 12 (December 2019) - Helme, Mark; Bishop, Christopher; Emmonds, Stacey; Low, Christopher
Abstract : Abstract: Helme, M, Bishop, C, Emmonds, S, and Low, C. Validity and reliability of the rear foot elevated split squat 5 repetition maximum to determine unilateral leg strength symmetry. J Strength Cond Res 33(12): 3269–3275, 2019—The purpose of this study was to examine the validity and reliability of the rear foot elevated split squat (RFESS) 5 repetition maximum (5RM) test as a field method for measuring unilateral leg strength symmetry. As a validated method of testing symmetry, the RFESS 5RM may be used by strength and conditioning coaches and sports medicine staff to measure the presence of imbalances with minimal equipment and time. Twenty-six subjects (age = 23.8 ± 4.6 years, mass = 88.1 ± 10.7 kg, and height = 1.79 ± 0.1 m) with a minimum 2 years of strength and conditioning experience were recruited. After a familiarization session, subjects performed an incremental 5RM protocol on both legs, on 2 occasions where 3D motion and force data were collected. Moderate reliability of bar load symmetry was found between test and retest conditions correlation (intraclass coefficient = 0.73, 0.33–0.91) with no proportional bias between sessions. Validation of the exercise was analyzed using a correlation between asymmetries in mean set vertical ground reaction forces (vGRF) of the lead foot during the concentric phase, with bar load. When all maximal trials, from both test conditions, were analyzed, a most likely large positive correlation (0.57, 0.30–0.76) was found for mean set concentric lead foot vGRF. When a threshold level of load symmetry (96.54–103.46%) was applied, a most likely large positive correlation ( r = 0.59, 0.14–0.84) between symmetry in lead foot vGRF was found in subjects who exceeded this limit. Conversely, analysis of subjects within the threshold produced unclear correlations. Findings of this study suggest the RFESS is a valid and reliable measure of unilateral leg strength symmetry. Practitioners are recommended to use this exercise to investigate the strength symmetry of athletes, but are guided to note that a threshold level of symmetry (96.54–103.46%) may be required to have been exceeded to indicate a true difference in vGRF production.